2005
DOI: 10.1039/b510891h
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of triblock copolymers and their homopolymers at laponite clay/solution interface. Role played by the copolymer nature

Abstract: The adsorption thermodynamics of copolymers, based on ethylene oxide (EO) and propylene oxide (PO) units, at the laponite (RD) clay/liquid interface was determined at 298 K. The copolymer nature was tuned at molecular level by changing the hydrophilicity, the architecture and the molecular weight (Mw) keeping constant the EO/ PO ratio. Polyethylene (PEGs) and polypropylene (PPGs) glycols with varying Mw and their mixture were also investigated to discriminate the role of the EO and the PO segments in the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…However, copolymer ATPS enable the application of the 1N2N, a water-insoluble extractant, since, as pointed out above, the phase enriched in macromolecules has high hydrophobicity. The reagent 1N2N forms highly stable complexes with several metal ions, such as Co(II), Cu(II), Fe(III) and Ni(II) [34] and it has higher selectivity and larger partitioning coefficient.…”
Section: Liquid-liquid Metal Ions Partitioning Studiesmentioning
confidence: 99%
“…However, copolymer ATPS enable the application of the 1N2N, a water-insoluble extractant, since, as pointed out above, the phase enriched in macromolecules has high hydrophobicity. The reagent 1N2N forms highly stable complexes with several metal ions, such as Co(II), Cu(II), Fe(III) and Ni(II) [34] and it has higher selectivity and larger partitioning coefficient.…”
Section: Liquid-liquid Metal Ions Partitioning Studiesmentioning
confidence: 99%
“…De Lisi et al studied the thermodynamics of adsorption of triblock copolymers (PEO-PPO-PEO) at the interface of Laponite ® clay/solution when varying the hydrophilicity, the architecture and the molecular weight of the copolymer [168]. Calorimetric results and modeling kinetic data indicated that the architecture of the copolymers did not have a significant influence on the interactions between the Laponite ® platelets and the copolymers.…”
Section: Polymer/clay Nanocompositesmentioning
confidence: 99%
“…They stabilize suspensions [1,2] and undergo aggregation processes that are very thermosensitive [3][4][5]. Therefore, these macromolecules are exploited for various applications (pharmaceutical formulations [6][7][8] and medical uses [6,9], removal of organic contaminants [10][11][12] from soil and water basins, etc.…”
Section: Introductionmentioning
confidence: 99%